Connection Amount Type Leukocytes on Student Faculty Medicine of Muslim University of Indonesia Based on Index Mass Body (IMT) - M Syahwal; Sri Julyani; Andi Alamanda Irwan; Irna Diyana Kartika; Nesyana Nurmadilla (Jurnal EduHealth, 2025)
Leukocytes play an important role in the body's immune response and can reflect a person's health condition, including the presence of infection or inflammation. In certain conditions, such as obesity, the number of types of leukocytes can change in response to inflammation that occurs in the body. The purpose of this study is to see connection amount type leukocytes with Index Mass Body (BMI) on student Faculty Medicine of Muslim University of Indonesia. Using method study quantitative with design cut cross sectional, with Technique Analysis Univariate and Multivariate. Results study show that, there was no relationship between BMI status and leukocyte count in students of the Faculty of Medicine, Muslim University of Indonesia. Researchers believe that a healthy lifestyle, higher levels of physical activity, and younger age may play a role in preventing significant inflammatory impacts in this population.